A novel imidazopyridine derivative, X22, attenuates sepsis-induced lung and liver injury by inhibiting the inflammatory response in vitro and in vivo - Ge X; Feng Z; Xu T; Wu B; Chen H; Xu F; Fu L; Shan X; Dai Y; Zhang Y; Liang G (Dove Medical Press, 2016)
Xiangting Ge,1,2,* Zhiguo Feng,1,* Tingting Xu,2 Beibei Wu,3 Hongjin Chen,1 Fengli Xu,3 Lili Fu,1 Xiaoou Shan,3 Yuanrong Dai,2 Yali Zhang,1 Guang Liang11Chemical Biology Research Center, School of Pharmaceutical Sciences, 2Department of Pulmonary Medicine, The 2nd Affiliated Hospital, 3Department of Pediatrics, The 2nd Affiliated Hospital, Wenzhou Medical University, Wenzhou, People’s Republic of China*These authors contributed equally to this workAbstract: Sepsis remains a leading cause of death worldwide. Despite years of extensive research, effective drugs to treat sepsis in the clinic are lacking. In this study, we found a novel imidazopyridine derivative, X22, which has powerful anti-inflammatory activity. X22 dose-dependently inhibited lipopolysaccharide (LPS)-induced proinflammatory cytokine production in mouse primary peritoneal macrophages and RAW 264.7 macrophages. X22 also downregulated the LPS-induced proinflammatory gene expression in vitro. In vivo, X22 exhibited a significant protection against LPS-induced death. Pretreatment or treatment with X22 attenuated the sepsis-induced lung and liver injury by inhibiting the inflammatory response. In addition, X22 showed protection against LPS-induced acute lung injury. We additionally found that pretreatment with X22 reduced the inflammatory pain in the acetic acid and formalin models and reduced the dimethylbenzene-induced ear swelling and acetic acid-increased vascular permeability. Together, these data confirmed that X22 has multiple anti-inflammatory effects and may be a potential therapeutic option in the treatment of inflammatory diseases.Keywords: LPS, imidazopyridine derivative, sepsis, acute lung injury, inflammation